(untitled) (Scientific journal of the Fergana State University, 2025)
This article discusses the use of interactive exercise machines in physical education classes at secondary schools to enhance the effectiveness of training sessions. First, the concept of interactive simulators, their potential integration into the educational process, and their role in increasing students’ interest in physical activities are explained. Then, both international and local scientific sources on the application of interactive training equipment are reviewed. The paper highlights how modern technology-based physical activities affect students’ healthy lifestyles, physical development, and motivation, drawing on the results of research. Finally, recommendations are provided for the broad implementation of interactive exercise machines in physical education lessons.